Nickel-catalyzed desulfonylative olefination of β-hydroxysulfones. Issue 6 (20th February 2023) - Cook, Adam; Bezaire, Maxwell; Newman, Stephen G.
Abstract : A Ni-catalyzed C–O bond activation is used to access alkenes directly from β-hydroxysulfones. Abstract : Disclosed herein is a protocol that permits the desulfonylative olefination of β-hydroxy, β-keto and β-ethereal sulfones through the activity of a Ni-NHC catalyst. Employing this method allows for the reliable synthesis of both nonconjugated and conjugated olefins with mono, di, tri or tetrasubstitution patterns. A brief mechanistic exploration of this reaction provides evidence to support the existence of both radical and organonickel intermediates en route to form product.